A influência de fatores localizacionais na internacionalização de uma empresa de país de economia emergente: o caso de uma empresa indiana de tecnologia de informação - Estrázulas, José Fernando Castro (2014)
The Internationalization, which occurs from the process interaction between organizations in different countries, is becoming more and more important in the corporate strategic context, once it represents a response to the globalization challenge. Due to the markets expansion, increased competition and the innovation cycle acceleration, companies need to be prepared to respond to the challenges that threaten their survival. The objective of this study is to investigate the internationalization of emerging economies companies, on a perspective of the influence of localization aspects. In light of this, the company selected for this study was Wipro Technologies, an Indian multinational that operates in the Information Technology sector, providing global outsourcing services. The study of the internationalization of firms from emerging economies and the factors related to the location is important both on a scientific perspective, once existing investigations have privileged the internationalization of developed countries companies, not focusing on the phenomenon from the perspective of emerging country companies (maybe due to the fact that they were rare in the past), and also on a business perspective, once it can help companies to develop their internationalization strategies. The study was carried out using a qualitative and descriptive methodology, with data obtained from semi-structured interviews with senior executives, supplemented by documents and direct observation at meetings in the company object of this study. The choice of the case allowed an interesting field of learning, first by the identification of the location factors that determined the internationalization strategy (past), and, second, the level of challenges that are currently posed to the company and possible answers. The results of this study contribute to the academy, once concludes that the internationalization process of Wipro, on one hand, can still be explained by the traditional internationalization theories, following progressive steps of internationalization, but, on the hand, cannot be fully explained by the Uppsala model, considering that internationalization did not start by a similar or smaller distance market both physical or psychological, as their domestic market. This study also concludes that there was a strong concern with the life quality of employees as a locational factor and the high agency influence in the internationalization decision, who was influenced by the familiarity with the local environment, allowing us to finalize this study stating that there was psychic distance reduction phenomenon in the internationalization process of Wipro to Brazil. Finally, this study interestingly observed the internacionalization to Brazil was motivated by economic reasons, however, the decision in favor of Curitiba as the center of operations was motivated by comportamental reasons.